Mutual Neutralization in Collisions of Li+ with O− - Åsa Larson; Ann E. Orel (Atoms, 2024)
The total and differential cross-sections and final state distribution for mutual neutralization in collisions of Li+ with O− were calculated using an ab initio quantum mechanical approach based on potential energy curves and non-adiabatic coupling elements computed with the multi-reference configuration interaction method. The final state distributions favored channels with excited oxygen states, indicating a strong effect of electron correlation, and the electron transfer could not be described by a simple one-electron exchange process.